Brain Source Correlates of Speech Perception and Reading Processes in Children With and Without Reading Difficulties - Azaiez, Najla; Loberg, Otto; Hämäläinen, Jarmo A.; Leppänen, Paavo H. T. (Frontiers in Neuroscience, 2022)
Neural correlates in reading and speech processing have been extensively addressed in the literature. Reading skills and speech perception have been shown to be associated, but their relationship remains debatable. In this study, we investigated reading skills, speech perception, reading, and their correlates with brain source activity in auditory and visual modalities. We used high-density event-related potentials (ERPs), fixation-related potentials (FRPs), and source reconstruction with the source reconstruction method. The analysis was conducted on 12–13-year-old schoolchildren who had different reading levels. Brain ERP source indices were computed from frequently repeated Finnish speech stimuli presented in an auditory oddball paradigm. Brain FRP source indices were also computed for words within sentences presented in a reading task. Our results showed significant correlations between speech ERP sources and reading scores at the P100 (P1) time range in the left hemisphere and the N250 time range in both hemispheres, and a weaker correlation for visual word processing N170 FRP source(s) in the posterior occipital areas, close to the visual word form areas (VWFA). Furthermore, significant brain-to-brain correlations were found between the two modalities, where the speech brain sources of the P1 and N250 responses correlated with the reding N170 response. Our results suggest that speech processes are linked to reading fluency, and that brain activations to speech are linked to visual brain processes of reading. These results suggest that a relationship between language and reading systems is present even after several years of exposure to print.